Makna “Lawero” Sebagai Simbol di Kota Baubau (Studi Komunikator Tokoh masyarakat Kota Baubau) - Wulan Kurniasari (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2016)
ABSTRACT Wulan Kurniasari.A, Stambuk C1D1 12 053. Meaning "Lawero" As a symbol in the city of Baubau (Study Communicators Baubau City community leaders), Supervising La Ode Jumaidin and Hasriani Amin. The problem of this research is no understanding of understanding, both community leaders or the general public about lawero which became one of the symbols in Baubau city that gave birth to symbolize different things between the people in the city Baubau. This study aims to identify and analyze the meaning lawero as a symbol in the city of Baubau. This paper is based on the theory of the symbol being addressed by Susanne Langer. This research method using descriptive qualitative method. Determination of informants by purposive sampling (intentionally). The data collected by observation, interview and documentation. This research shows that, Statues Lawero tail shows the tail end of the upright leads to the ground. And the head of the statue shows the face and abdomen Lawero lawero of land. Describing animal resembling a dragon, are very large and able to redeem a layer of soil, air and sea, in charge of guarding and protecting people and communities Baubau city so as to create wealth and prosperity together. Keywords ; Prosperity and Welfare